Orientacoes superiores: Time and bureaucratic authority in Mozambique - Gonçalves, Euclides (African Affairs, 2013)
This article examines the production, circulation, and interpretation of regulatory documents in contemporary Mozambique in order to highlight their central importance to processes of governance. The empirical focus is on orientações superiores – written and oral documents issued by ﬁgures and institutions of authority with the intention of advising on procedures for policy formulation and implementation. By producing orientações superiores in a way that leaves their intent ambiguous and their status provisional, party and state ofﬁcials shift the focus of policy making from substance to process. In this way, bureaucratic authority is produced and reinforced through the manipulation of the timing of policy implementation. This perspective expands current understandings of African governance that on the whole have been limited to the analysis of the effectiveness of African institutions and policies, leaving the tactical effects of ambiguity, timing, and provisionality in policy implementation undertheorized.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - ethnography / etnografia; authority / autoridade

Facing the forest entrepreneurs - Healy, Hazel (New Internationalist, 2013)
Communities are scrambling to protect their lands from the tree plantations multiplying across Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra

‘Operation of the Market's Study. How the poor access, hold and trade land: Findings from research in two settlements in Tete, Mozambique - Gordon, Ross; Taljaard, Reathe; Massuanganhe, Egildo, Egildo (Progressus Research Development Consultancy, 2013)
The way in which informal land transactions occur and the extent to which they result in tenure security and asset creation in these informal settlements is not well understood. For this reason this study comprises research into two informal settlements (namely Matundo and Mateus Sansão Muthemba [Sansão Muthemba]) in Tete, Mozambique, so as to understand how the poor access, hold and trade land. This research forms part of a larger research programme being undertaken by Urban LandMark which includes similar studies in Lilongwe (Malawi), Maputo (Mozambique), Luanda (Angola) and Durban, Cape Town and Johannesburg (South Africa). Reports on these other research projects can be seen on www.urbanlandmark.co.za.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; governance / governação; land governance / gestão de terra